A pilot study to evaluate urine LAM assay for diagnosis of pulmonary tuberculosis among non-HIV patients. (October 2020) - Gupta, Akshita; Kumar, Ajay; Ashraf, Asem Ali; Madigubba, Haritha; Chawla, Kiran
There is a great need to improve diagnostic tools for tuberculosis where the majority are without HIV co-infection in resource-poor settings and high-burden areas such as India. The urine LAM assay has not hitherto been studied and may have a role to play. Our study found that, as a stand-alone diagnostic tool, the assay was suboptimal when compared to Xpert MTB/Rif. However, a combination of LAM assay along with sputum microscopy may be useful in settings where molecular testing is unavailable.